If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1y = -26 + 7y Solving 9 + -1y = -26 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 9 + -1y + -7y = -26 + 7y + -7y Combine like terms: -1y + -7y = -8y 9 + -8y = -26 + 7y + -7y Combine like terms: 7y + -7y = 0 9 + -8y = -26 + 0 9 + -8y = -26 Add '-9' to each side of the equation. 9 + -9 + -8y = -26 + -9 Combine like terms: 9 + -9 = 0 0 + -8y = -26 + -9 -8y = -26 + -9 Combine like terms: -26 + -9 = -35 -8y = -35 Divide each side by '-8'. y = 4.375 Simplifying y = 4.375
| 7(2+3x)-5=114 | | (2x+1)*(3x^2+2x+1)=0 | | -2(1-6x)=82 | | 2=log(4) | | -14-16+x=6 | | 3x+5=3x+5*2 | | 1/2(126) | | -x+7y=26 | | 3x+5=3x+58*10 | | 3F-12=3(F-1612) | | 2x+x+31=124 | | 4(v+3)=7v-12 | | -5(-4-2x)=100 | | F(x)=x^4-5x^2+1 | | 2b-7=12 | | -3u-42=-6(u+2) | | (3x+8)(5x^2+2x+5)= | | 180=90+3x+2+x | | 1040=x+y | | -18=4v+2(v+6) | | Log[3](4x+1)=3 | | (6+9i)-(-8+I)= | | 5.8x+14=2x+22 | | 4+2m-3= | | 7n-7=5n | | -14=2(u-4)-5u | | 32x-7+8=32 | | y=(3x-15)/4 | | 32x-7+8=16 | | y=(15-3x)/4 | | (ln793-1)/-5 | | 16x-7+8=32 |